An improved seagull optimization algorithm for optimal coordination of distance and directional over-current relays - Abdelhamid, Mohamed; Houssein, Essam H.; Mahdy, Mohamed A.; Selim, Ali; Kamel, Salah (Expert systems with applications, 2022)
In this paper, an improved bio-inspired optimization algorithm called Seagull Optimization Algorithm (ISOA) is proposed. ISOA is developed based on three techniques, these techniques use the collaborative optimization strategy, simulating new bird’s generation, and rearranging subgroups. The CEC2020 is utilized to obtain the role and importance of the improved algorithm. Furthermore, the ISOA is applied to find the optimal coordination of Distance and Directional Over-Current Relays (D&DOCRs). The problem of D&DOCRs coordination is more complicated and has numerous constraints. Hence, in this work, a developed object function (DOF) is proposed to set the Distance relays with minimum available settings. ISOA and DOF are tested on the IEEE 8-bus and IEEE 14-bus test systems. ISOA algorithm is used to coordinate the D&DOCRs in both the near and far ends of transmission lines. The results of test systems prove the effectiveness of ISOA to solve the coordination of D&DOCRs using the DOF. •Improving the original seagull optimization algorithm (ISOA).•Developing the object function (DOF) to be simpler and with fewer constraints.•Testing the improved algorithm (ISOA) on CEC2020 benchwork.•ISOA-DOF is used to solve coordination problem of D &DOCRs protection.